Suppressing Edge Back-Scattering of Electromagnetic Waves Using Coding Metasurface Purfle - Li, Xinghua; Feng, Mingde; Wang, Jiafu; Meng, Yueyu; Yang, Jiaheng; Liu, Tonghao; Zhu, Ruichao; Qu, Shaobo (Frontiers in Physics, 2020)
Edge scattering is one of the main scattering sources for metal objects, especially for those with thin front edges. In this paper, we propose to suppress the edge back-scattering of electromagnetic (EM) waves using coding metasurface purfle, which based on the principle of scattering cancellation, rather than absorption. To this end, two split-ring resonators (SRRs) are designed to have a π phase difference, as the 0- and 1-element of the coding metasurface. The coding metasurface is fixed on the front edge of a thin metal plate, and the back-scattering of front edge is significant for EM waves polarized along the edge direction. Due to the anti-phase scattering of the two coding elements, the back-scattering of the edge is suppressed by right of the scattering cancellation along the normal of the edge. Both the simulation and experiment results verify the reduced back-scattering of the flat edge. A maximal reduction of 24dB is attained within the central frequency of about 11 GHz. This work provides a new way of suppressing edge scattering and may find applications in EM compatibility, radar stealth technologies, etc.